The memory sessions : a memoir - Farrell Smith, Suzanne (Bucknell University Press, 2019)
"Suzanne Farrell Smith's father was killed by a drunk driver when she was six, and a devastating fire nearly destroyed her house when she was eight. She remembers those two--and only those two--events from her first nearly twelve years of life. While her three older sisters hold on to rich and rewarding memories of their father, Smith recalls nothing of him. Her entire childhood was, seemingly, erased. In The Memory Sessions, Smith attempts to excavate lost childhood memories. She puts herself through multiple therapies and exercises, including psychotherapy, hypnotherapy, somatic experiencing, and acupuncture. She digs for clues in her mother's long-stored boxes. She creates--with objects, photographs, and captions--a physical timeline to compensate for the one that's missing in her memory. She travels to San Diego, where her family vacationed with her father right before he died. She researches, interviews, and meditates, all while facing down the two traumatic memories that defined her early life. The result is an experimental memoir that upends our understanding of the genre. Rather than recount a childhood, The Memory Sessions attempts to create one from research, archives, imagination, and the memories of others. Published by Bucknell University Press. Distributed worldwide by Rutgers University Press"--